Radiographic predictors for improved outcomes after hammertoe correction surgery. Issue 3 (14th September 2018) - Maidman, Samuel; Bariteau, Jason; Boden, Stephanie; Boden, Allison; Tenenbaum, Shay
Category: Lesser Toes Introduction/Purpose: Hammertoe deformities are common, often painful deformities of the lesser foot and are known to severely affect daily activities. When patients seek surgical management, x-rays are utilized for diagnosis, evaluation for surgical candidacy, and selection of the operative technique. Postoperatively, radiographs are retaken to assess bone health, healing status, and alignment. Despite the frequent use of radiographs pre- and post-operatively, radiographic results are not necessarily indicative of clinical presentation or surgical outcomes. The aim of this study is to identify specific radiographic parameters that are predictive of improved pain and function after surgical correction of hammertoe deformity. Methods: Prospectively collected data was reviewed on 51 consecutive patients who underwent operative correction of hammertoe deformity. Patient demographics, comorbidities, and post-surgical complications were recorded from their electronic medical records. Clinical outcomes were assessed utilizing preoperative and postoperative Visual Analogue Scale (VAS) and Short Form Health Survey Physical Component (SF-36 PCS) scores with a minimum of six-month follow-up. Radiographs were scored by a foot & ankle fellowship-trained orthopaedic surgeon to assess preoperative severity, postoperative joint fusion, and both pre- and postoperative joint instability and arthritis. Data was examined using a multivariable analysis. Results: Preoperatively, 15.7% (8/51) of patients had a deformity classified radiographically as mild, 37.3% (19/51) as moderate, and 47.1% (24/51) as severe. Additionally, 60.8% (31/51) had joint instability, 17.7% (9/51) had joint dislocation, and 7.8% (4/51) had joint arthritis. Postoperatively, 74.5% had PIP joint fusion, 35.3% (18/51) had joint arthritis, and 9.8% (5/51) had joint instability. A significant association was found between PIP joint fusion and improved SF-36 PCS scores (p=.004). Preoperative anticoagulant therapy was associated with reduced rates of PIP joint fusion (p=0.02). There was no association found between the other demographic or radiographic parameters, and no parameters were associated with improvement in VAS scores. Conclusion: After undergoing surgical correction of hammertoe deformity, postoperative PIP joint fusion was the only variable determined to be indicative of improved physical function. However, pre- and postoperative metatarsophalangeal joint arthritis nor instability was predictive of outcomes. This work informs foot & ankle specialists that healing of the PIP joint is critical to successful hammertoe surgery.